1995
DOI: 10.1056/nejm199508243330802
|View full text |Cite|
|
Sign up to set email alerts
|

Resistance to Penicillin and Cephalosporin and Mortality from Severe Pneumococcal Pneumonia in Barcelona, Spain

Abstract: Current levels of resistance to penicillin and cephalosporin by S. pneumoniae are not associated with increased mortality in patients with pneumococcal pneumonia. Hence, these antibiotics remain the therapy of choice for this disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

25
310
2
32

Year Published

1998
1998
2013
2013

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 689 publications
(369 citation statements)
references
References 36 publications
25
310
2
32
Order By: Relevance
“…However, retrospective and prospective studies in adult and pediatric populations showed that the outcomes of pneumococcal pneumonias caused by purportedly resistant strains but treated with penicillin antibiotics did not differ from those obtained with other antimicrobial agents, suggesting that meningitis breakpoints did not apply to pneumonia. [12][13][14] Later multicenter studies confirmed these results. 15,16 On the basis of these findings and of a review and S. pneumoniae strains were isolated from blood cultures using the BacT/ALERT ® detection system (Biomérieux, France), whereas pleural fluid specimens were cultured on chocolate agar and sheep blood agar (Biomérieux, Rio de Janeiro, Brazil).…”
Section: Introductionmentioning
confidence: 67%
“…However, retrospective and prospective studies in adult and pediatric populations showed that the outcomes of pneumococcal pneumonias caused by purportedly resistant strains but treated with penicillin antibiotics did not differ from those obtained with other antimicrobial agents, suggesting that meningitis breakpoints did not apply to pneumonia. [12][13][14] Later multicenter studies confirmed these results. 15,16 On the basis of these findings and of a review and S. pneumoniae strains were isolated from blood cultures using the BacT/ALERT ® detection system (Biomérieux, France), whereas pleural fluid specimens were cultured on chocolate agar and sheep blood agar (Biomérieux, Rio de Janeiro, Brazil).…”
Section: Introductionmentioning
confidence: 67%
“…(22) There are conflicting data on whether this type of resistance correlates with clinical failure among patients with invasive pneumococcal disease treated with macrolide antibiotics. (7,9,10,13,17,23,24) The strongest predictor of macrolide resistance among patients with pneumococcal bacteremia was prior antibiotic use. Patients who have received > 24 hours of antibiotics therapy at the time the blood culture was drawn were four times more likely to harbor a macrolide resistant organism, compared to those not receiving prior antibiotic therapy.…”
Section: Discussionmentioning
confidence: 99%
“…There is literature suggesting that antibiotic resistance may contribute to treatment failure and poor clinical outcomes. (7,(9)(10)(11) Cases of failed therapy in association with resistance have been reported, but large-scale clinical studies of this phenomenon are lacking. The result is poor consensus regarding the clinical implications of antimicrobial resistance.…”
Section: Introductionmentioning
confidence: 99%
“…A diferencia de varios reportes internacionales 12,13 , en el curso de nueve años no hemos observado tendencia al aumento en la frecuencia de cepas con resistencia a PNC. Durante el año 2003, las cepas de susceptibilidad disminuida a la PNC alcanzaron a 13,7%, cifra similar a la ya observada los años 2000 y 1997.…”
Section: Discussionunclassified